ANALISIS HUBUNGAN PENGETAHUAN DAN SIKAP WANITA YANG TELAH MENIKAH DENGAN PEMERIKSAAN KEHAMILAN TEST DI WILAYAH KERJA KOTA BINJAI TAHUN 2019 - RAISAH DEWI (JURNAL ILMIAH MAKSITEK, 2020)
In Indonesia, it is estimated that 15,000 new cases of cervical cancer each year with a death rate of about 7,500 cases per year. From the initial survey conducted at the Puskesmas it was found that more than 50% of mothers did not know that there was an examination and some felt afraid and taboo to be examined even though there were complaints of vaginal discharge and were suspected of being due to the mother's lack of knowledge. This study aims to determine the relationship between the level of knowledge and attitudes of married women and the pregnancy test in the Binjai City work area in 2019.Knowledge is the factor most closely related to the pregnancy test in the Binjai City work area in 2019. It is hoped that the Puskesmas will provide comprehensive and continuous information, increase knowledge about pregnancy and Pap's smears by making posters and information that can be read as well as health education and procurement of examination programs with the Pregnancy method.Pregnancy that is done precisely in the third week at a low cost so that all people with low economies can get checked out to prevent cervical cancer. Binjai Regional Hospital has socialized the Pregnancy program to prevent uterine cancer and in every corner of the room there is information about pregnancy.However, these mothers are still reluctant to have their reproductive organs checked because they are afraid if cervical cancer is found because they are not ready to suffer from cervical cancer, another reason is that women of childbearing age feel taboo to open their lower parts (vaginal organs) and feel embarrassed. seen by others. Husbands also never support or advise their wives and ask questions about the pregnancy